Pengetahuan, Kecemasan Masyarakat dalam Menghadapi COVID-19 - Maria Haryanti Butarbutar; Herianto Bangun; Jessica Tarihoran; Endang Sihaloho; Rini Sara Panjaitan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the frequency distribution of knowledge and community anxiety in dealing with COVID-19 in Huta IV Jawadipar. The research design used in this study uses the Analytical Survey method with a Cross-Sectional approach. The results showed that knowledge about preventing transmission of COVID-19 was in a suitable category by 28 (56%), and attitudes about preventing transmission of COVID-19 were in a suitable category by 28 people (56.0%). Moderate anxiety for as many as 31 people (50%). In conclusion, statistically, there is a relationship between knowledge and public pressure in dealing with COVID-19 in Huta IV Jawadipar Keywords: COVID-19, Knowledge, Behavior, Attitude